Sustainable Solar Energy Through PV Net Metering Systems: A Roadmap for Bangladesh - Khan, Md. Ayaj Uddin; Khandaker, Nadim Reza (Journey for Sustainable Development and Peace Journal, 2026)
The primary purpose of this research is to assess the current state of photovoltaic (PV) net metering (NEM) systems in Bangladesh and explore their potential to contribute to rural electrification. The methodology involves a comprehensive review of existing policies, technologies, and market trends, alongside an analysis of the barriers to widespread PV NEM adoption. The study identifies key challenges, including high upfront costs, limited financing options, technical integration issues with the grid, and socio-cultural resistance, particularly in rural areas. Despite these barriers, the findings highlight the rapid growth of solar adoption through government programs, such as Solar Home Systems (SHS) and large-scale solar projects. The research concludes that to maximize the benefits of PV NEM, policy reforms are necessary, including financial incentives, simplified approval processes, and increased public-private partnerships. The implications suggest that overcoming financial, technical, and social obstacles can unlock Bangladesh’s renewable energy potential, supporting both economic development and environmental sustainability. This study is crucial for informing future policy and investment strategies in Bangladesh and similar regions with limited access to energy.